Pengaruh Modal Usaha, Lokasi Usaha Dan Teknologi Informasi Terhadap Pendapatan Umkm Pada Kecamatan Alok - Herodian, Alvita Virgine; Dince, Maria Nona; Da Silva, Yustina Olivia (Jurnal Projemen UNIPA, 2025)
This research aimed to investigate the impact of business capital, business location, and information technology on the income of MSMEs. The data collection techniques used in this research were interviews, observation, documentation, and questionnaires. The type of research was quantitative research. The data analysis techniques used in this research were data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results indicated that business capital (X') significantly affects MSME income (Y), business location (X²) significantly affects MSME income (Y), information technology (X') significantly affects MSME income (Y), and simultaneously, all three independent variables, namely business capital, business location, and information technology, significantly affect MSME income